Experimental and Numerical Correlation of Impact of Spherical Projectile for Damage Analysis of Aero Engine Component - Majila, Anuradha Nayak; Jain, Rajeev; Fernando D., Chandru; Ramachandra, S. (Defence Science Journal, 2016)
Studies the impact response of flat Titanium alloy plate against spherical projectile for damage analysis of aero engine components using experimental and finite element techniques. Compressed gas gun has been used to impart speed to spherical projectile at various impact velocities for damage studies. Crater dimensions (diameter and depth) obtained due to impact have been compared with finite element results using commercially available explicit finite element method code LS-DYNA. Strain hardening, high strain rate and thermal softening effect along with damage parameters have been considered using modified Johnson-Cook material model of LS-DYNA. Metallographic analysis has been performed on the indented specimen. This analysis is useful to study failure analysis of gas turbine engine components subjected to domestic object damage of gas turbine engine.